Small Fibre Neuropathy Is Associated With Impaired Vascular Endothelial Function in Patients With Type 2 Diabetes - Ando, Akihiko; Miyamoto, Michiaki; Saito, Naoko; Kotani, Kazuhiko; Kamiya, Hideki; Ishibashi, Shun; Tavakoli, Mitra (Frontiers in Endocrinology, 2021)
Diabetic polyneuropathy (DPN) and endothelial dysfunction are prevalent complications of diabetes mellitus. Currently, there are two non-invasive markers for endothelial dysfunction: flow-mediated dilation and reactive hyperaemia peripheral arterial tonometry (RH-PAT). However, the relationship between diabetic small fibre neuropathy and macroangiopathy remains obscure thus far. Corneal confocal microscopy (CCM) has emerged as a new diagnostic modality to assess DPN, especially of small fibre. To clarify the relationship between diabetic small fibre neuropathy and vascular dysfunction, we aimed to determine the functions of peripheral nerves and blood vessels through clinical tests such as nerve conduction study, coefficient of variation in the R-R interval, CCM, and RH-PAT in 82 patients with type 2 diabetes. Forty healthy control subjects were also included to study corneal nerve parameters. Correlational and multiple linear regression analyses were performed to determine the associations between neuropathy indices and markers for vascular functions. The results revealed that patients with type 2 diabetes had significantly lower values for most variables of CCM than healthy control subjects. RH-PAT solely remained as an explanatory variable significant in multiple regression analysis for several CCM parameters and vice versa. Other vascular markers had no significant multiple regression with any CCM parameters. In conclusion, endothelial dysfunction as revealed by impaired RH-PAT was significantly associated with CCM parameters in patients with type 2 diabetes. This association may indicate that small fibre neuropathy results from impaired endothelial dysfunction in type 2 diabetes. CCM parameters may be considered surrogate markers of autonomic nerve damage, which is related to diabetic endothelial dysfunction. This study is the first to report the relationship between corneal nerve parameter as small fibre neuropathy in patients with type 2 diabetes and RH-PAT as a marker of endothelial dysfunction.